PERANAN KEPERCAYAAN DALAM MEMODERASI KUALITAS LAYANAN DAN BRAND IMAGE TERHADAP MINAT KUNJUNG ULANG PASIEN PADA RSUD ASEMBAGUS SITUBONDO - Royvih Bachtiar; Yudha Praja; Rini Kartika Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The aim of this research is to determine the role of trust in moderating the influence of service quality and brand image on patients' intention to revisit patients at Asembagus Situbondo Regional Hospital. The background to this research stems from the importance of improving service quality and strengthening the hospital's image in creating patient loyalty. This research used a quantitative approach with a simple random sampling technique for 98 patients who had received services at the Asembagus Situbondo Regional Hospital. Data analysis and hypothesis testing were carried out using Structural Equation Modeling – Partial Least Squares (PLS-SEM). The research results show that service quality has a positive and significant influence on patients' intention to revisit, while brand image actually shows a significant negative influence on intention to revisit. In addition, trust is proven to significantly moderate the relationship between service quality and intention to revisit, meaning that the higher the patient's trust, the stronger the influence of service quality on intention to revisit. Trust also positively moderates the relationship between brand image and revisit intention. These findings confirm that trust has an important role in strengthening the relationship between service marketing factors and patient intention to return to use hospital services.